Trace determination of phenanthrene and fluorene in beverages using D-μ-SPE and liquid chromatography analysis - Anis, Ahmad Lutfi; Kamaruzaman, Sazlinda; Kamaruzaman, Sazlinda; Zaini, Nurzaimah; Mohammad Anwar, Farahnaz; Wan Ibrahim, Wan Nazihah; Mohamad Hanapi, Nor Suhaila (Akademi Sains Malaysia, 2024)
Dispersive micro solid phase extraction (D-μ-SPE) method using Graphene Oxide (GO) for the extraction and pre-concentration of selected polycyclic aromatic hydrocarbons (PAHs) from beverage samples prior to high-performance liquid chromatography - diode array detector (HPLC - DAD) is reported. Selected PAHs Fluorene (FLU) and Phenanthrene (PHE) were used as targeted analytes. An experimental design using Response Surface Methodology (RSM) and Box–Box–Behnken design (BBD) was performed to evaluate the interactive effects of three significant parameters: mass of sorbent, sample volume and extraction time. Under the optimum conditions, the method revealed good linearity (R2 = 0.9995 – 0.9998) over a concentration range of 0.5 – 5.0 mg L-1. The limit of detection (LOD) was in the range of 0.03 – 0.24 mg L-1 with satisfactory relative recoveries (81 – 99 %) and good relative standard deviation (RSD) of ≤ 3.80 % (n = 3). The method was successfully applied to tea, coffee, and milk samples and proved to be a simple, rapid, and reliable method with good extraction efficiencies for the detection of PAHs in beverage samples. © (2024), (Akademi Sains Malaysia). All Rights Reserved.